Blue Economy and Ocean Sustainability: A Bibliometric Review of Global Research - Hutajulu, Halomoan (Eastasouth Institute, 2025)
The blue economy has emerged as a crucial framework for balancing economic development and marine sustainability. This study employs a bibliometric analysis using data from Scopus and VOSviewer to examine global research trends in the blue economy and ocean sustainability. The findings reveal a rapid increase in scholarly interest, particularly in governance, marine policy, environmental economics, and climate change adaptation. Key contributing countries include the United States, United Kingdom, and Australia, while financial instruments such as blue bonds and sustainable investment funds are gaining prominence as emerging research themes. The study also highlights a shift towards equity and inclusivity in blue economy discussions, addressing socio-economic challenges in marine industries. Despite significant advancements, knowledge gaps persist regarding the effectiveness of governance frameworks, accessibility of financial mechanisms, and social equity. This study contributes to the literature by providing a comprehensive analysis of research trajectories, identifying future research directions, and emphasizing the need for interdisciplinary approaches in achieving a sustainable and inclusive blue economy.